Luxury brand attachment: Predictors, moderators and consequences. (22nd March 2022) - Shimul, Anwar Sadat; Phau, Ian
Abstract: Although there is ample evidence that consumer attachment varies across luxury and non‐luxury brands, there is a lack of research in understanding the predictors, moderators and consequences of luxury brand attachment (LBA). This paper aims to develop and test a research model for LBA (study 1), examine the moderating influence of self‐consciousness on the relationship between actual/ideal self‐congruence and LBA (study 2) and validate the research model across privately and publicly consumed products (study 3). Data ( n  = 961) were analysed using Structural Equation Modelling with the IBM SPSS AMOS 25.0. The results show that consumers' perceived actual and ideal self‐congruence have a significant positive impact on LBA. In addition, LBA results in consumer advocacy. Private (public) self‐consciousness enhances the relationship between actual (ideal) self‐congruence and LBA. However, social anxiety did not influence the relationship between self‐congruence and LBA. Moreover, the relationship between actual self‐congruence and LBA was stronger for privately consumed products. This research would provide luxury managers with an understanding of how consumers develop a bond with luxury brands based on the perceived brand self‐congruence. The LBA model would also help managers segment luxury consumers and identify the segments with low, medium and high attachment. In addition, using the findings of this research, luxury managers can incorporate the relevant aspect of self‐congruence into brand positioning and advertising messages.